Pengaruh Aksesibilitas terhadap Pengembangan Wilayah Pada Jalan Penghubung Pusat Kota Karebosi dengan Sub-urban Kawasan Tanjung Bunga, Kota Makassar - Rivani Ramadhani; Ananto Yudono; Arifuddin Akil (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2019)
Based on field facts, the road network system in the center of Makassar is more dominant than the suburbs (tanjung bunga area). This has an impact on the difficulty of accessing several areas that are close together but not connected. The purpose of this study was to determine the level of accessibility and level of regional development on the central connecting road of Makassar City with the Tanjung Bunga suburb and the relationship between the two variables. Data analysis techniques used include, calculation of the alpha index (α), Location Quotient (LQ), and calculation of the correlation between α with LQ, AHP and SWOT. Based on the results of the analysis it is known that the accessibility index is included in the category of high accessibility, LQ is included in the high category, regional accessibility and regional development have a direct relationship, that is, if regional accessibility experiences development, regional development will experience the same thing. As for the direction of the development, among others, the design of the station relating to people who visit with clarity of passenger circulation, planning the ring road, planning the connectivity of arterial roads, the realization of ring road construction, and making the Makassar City RTRW as a guide and integrated with regulations in planning the basic components of the train station fire.